(untitled) (Conferencea, 2022)
The organization of Veterinary and sanitary measures on the basis of modern scientific technologies, replenishing the composition of herd with healthy goods in Farmer farms, increasing the productivity of animals is an indicator of reducing the degree of morbidity.